Facts, Fake News, and COVID-19 Vaccination. Issue 2 (March 2022) - Rohan, Annie J.
Abstract : Social media is often a negative factor in patients having access to evidence-based facts about their health, such as the overwhelming benefits of COVID-19 vaccination for virtually all, including those who are considering pregnancy, are pregnant, lactating, or postpartum. Nurses continue to be the most trusted profession and have a vital role in sharing accurate information with patients about important preventative health treatments.